The Effect of Audiovisual Media on Anemia Prevention on Increasing Pregnant Women’s Knowledge in the Ciwaruga Public Health Center Area - Lisbet Octovia Manalu; Ika Basri; Ahmad Arifin (Health Dynamics, 2026)
Background: Anemia in pregnant women remains a health problem that can affect the health of both the mother and the fetus. One important factor in preventing anemia is the level of knowledge among pregnant women. Lack of knowledge can cause pregnant women to fail to recognize the signs and symptoms of anemia, which can result in delays in seeking health services and appropriate treatment. If anemia is not detected and treated early on, it can develop into severe anemia, which can increase the risk of pregnancy complications. This study aims to determine the effect of audiovisual media on anemia prevention in increasing the knowledge of pregnant women in the Ciwaruga community health center area. Methods: This study used a quantitative, pre-experimental design with a one-group pre-test and post-test. The study sample consisted of 37 pregnant women selected using accidental sampling. Results: There was an increase in pregnant women’s knowledge of anemia prevention. The Wilcoxon test showed a difference in knowledge levels, with a p-value < 0.001 (p < 0.05). Conclusion: Audiovisual media were effective in increasing pregnant women’s knowledge about anemia.